Pengaruh Limbah Tutup Botol Air Mineral Pada Lapis Perkerasan Base A - Sigit Harianto; Sazuatmo Sazuatmo; Elly Tripujiastutie (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2023)
One of the wastes that can be used as additives in base A is mineral water bottle caps. This waste can be expected to reduce the use of natural materials and reduce the amount of plastic waste. This study aims to determine the CBR value after adding mineral water bottle cap